(untitled) (Scientific journal of the Fergana State University, 2023)
The article for the first time brings into scientific circulation new archaeological materials of the Bronze Age, found during the exploration of the Zarafshan Valley. On the basis of modern radiocarbon analysis, the chronological date of the burials of the Andronovo culture has been clarified. It is noted that the pastoralists of the Afanesovо and Andronovо steppes and the bearers of the settled agricultural culture had long-standing cultural and economic ties in the funeral rite and ritual ceremony.